Digital games as an assistive technology resource in the literacy of students with autism spectrum disorder (Human Factors in Design, 2023)
With the use of assistive technology in education, the possibility of students with the disorder having better learning conditions is increased. The objective of this study is to identify in which aspects digital games favor the literacy process of students with autism spectrum disorder. The study was based on qualitative, descriptive and bibliographical research. Six digital games focused on children's literacy were evaluated by six basic education teachers. It was observed, with the result of data collection, that the selected games are suitable for children with autism spectrum disorder and contribute to the literacy process.
Keywords: Literacy; basic education; inclusive education